Developing a Blueprint for English Proficiency Test with Vocational Nuance Based on CEFR - Gullit Tornado Taufan; Rizqi Febrian Pramudita; Meiga Rahmanita; Nur Afni Rachman; Astrid Hidayanti Ananda Putri (Transpublika Publisher, 2025)
Standardized English proficiency test has been an essential part in English language teaching. Despite the fact that globally recognized tests such as TOEFL, IELTS, and TOEIC are, still, dominating, a number of institutions in Indonesia have started to administer their English proficiency tests. One of which is Politeknik Negeri Jember (Polije), a higher educational that focuses on vocational education. In line with its characteristics, developing standardized English proficiency test with vocational nuance should be more acceptable. Therefore, the development of the blueprint of English proficiency test with vocational nuance is conducted through this research and development (R&D). In this case, the blueprint is based on the Common European Framework of Reference as the basis of the development. The initial stage of the development, which focused on the analysis of important aspects of the development of the blueprint, has been completed. The stage is followed by the development stage, which is mainly discussed in this report, by considering the development aspects necessary for the new blueprint. As a result, the new blueprint of EPT Polije is developed and ready to be implemented.